A narrative review of pox: smallpox vs monkeypox - Samiksha Jayswal; Jagdish Kakadiya (SpringerOpen, 2022)
Abstract The famed variola (smallpox) virus and the monkeypox virus (MPXV) are closely related, and MPXV causes a milder form of febrile rash disease in people. Human monkeypox was mostly an uncommon zoonotic illness that was restricted to West and Central African wooded areas in the twentieth century. The global population's smallpox vaccine-induced immunity, however, has started to decrease as the number of cases and the geographic breadth have both increased significantly in this century. Several countries have seen human monkeypox outbreaks since May 2022. A possible shift in the monkeypox transmission pattern that might represent a bigger worldwide danger is raised by the atypical nature of these outbreaks, which are characterized by their high-case numbers and absence of ties to endemic countries. Here, we explore a wide range of MPXV biology topics.